Factors Affecting the Ground Penetrating Radar (GPR) Dataset - Wahab, Warishah Abdul; Zakaria, Wan Zaini; Omar, Rohayu Che; Jaafar, Jasmee; Taha, Hairin; Roslan, Rasyikin (International Journal of Psychosocial Rehabilitation, 2020)
The existing data on a subsurface utility that includes depth, position, type and material is essential information for any land development specifically involving subsurface utility maintenance, installation, and construction project. Incorrect information may result in possible damage to the subsurface utility during land development activities. Several non-destructive methods were developed in recent years to detect subsurface objects. Ground Penetrating Radar (GPR) is one of the latest technology to be used to detect subsurface utilities. This technique penetrates the subsurface and identifies the object below the ground by radio wave method, including the traces of metallic and non-metallic material at a precise location. Although this method provides an excellent advantage for the related sector, nonetheless, the surveyor needs to consider several factors such as the time window and point interval before using GPR for the detection task. This study investigates the impact of the antenna frequency, equipment parameters, and the depth of underground utility on the GPR observation results in term of accuracy. The results showed that the GPR image and the hyperbola form of the pipe influenced by the different antenna frequency, equipment parameter setting (time window and point interval), different GPR models and the depth of the buried pipeline.